Protocol for development, calibration and validation of the Patient-Reported Inventory of Self-Management of Chronic Conditions (PRISM-CC) - Tara Sampalli; Kylie Peacock; Tanya Packer; George Kephart; Åsa Audulv; America Keddy; Grace Warner (BMJ Open)
Introduction Assessing and measuring patients’ chronic condition self-management needs are critical to quality health care and to related research. One in three adults around the world live with multiple chronic conditions. While many patient-reported measures of self-management have been developed, none has emerged as the gold standard, and all have one or more of the following limitations: (1) they fail to measure the different domains of self-management important to patients, (2) they lack sufficient specificity to support patient-centred care or identify the specific components of self-management interventions that work and/or (3) they lack suitability for patients with multiple chronic conditions.Methods and analysis The Patient-Reported Inventory of Self-Management of Chronic Conditions (PRISM-CC) is being developed to overcome these shortcomings. It will measure respondents’ perceived success (or difficulty) in self-managing seven domains important to patients. The protocol has three phases. Phase 1 is conceptual model development and item generation. Phase 2 is assessment of the relevance and understanding of items by people with chronic conditions. Phase 3 is item analysis, dimensionality assessment, scaling and preliminary validation of the PRISM-CC using an online survey of people with chronic conditions (n~750). The expected completion date is early 2021.Ethics and dissemination This study will adhere to the Canadian Tri-Council Policy Statement on Ethical Conduct for Research Involving Humans. Ethics approval for all phases has been obtained from the Nova Scotia Health Authority Research Ethics Board. Once completed, the PRISM-CC will be made available for research and healthcare at minimal to no cost.